find the value if x=-3
![p(x) = x ^{3} + x ^{2} - 9x - 9 p(x) = x ^{3} + x ^{2} - 9x - 9](https://tex.z-dn.net/?f=p%28x%29+%3D+x+%5E%7B3%7D++%2B+x+%5E%7B2%7D++-+9x+-+9)
Answers
Answered by
0
Given,
If x = (-3); then,
HOPE THIS COULD HELP!!!
saltlake:
wrong answer
Answered by
1
Answer:
hii.
Step-by-step explanation:
given equation here..
p(x)= x^3+x^2-9x-9.
now put here..
x=-3
then ,
p(-3)= (-3)^3+(-3)^2-9*(-3)-9
p(-3)= -27+9+27-9
p(-3)=0.
I hopes its helps.
✨✨✨✨✨✨✨✨
please follow me!!✌️✌️
✨✨✨✨✨✨✨✨
Similar questions